2007
DOI: 10.1075/idj.15.3.02gra
|View full text |Cite
|
Sign up to set email alerts
|

Discourse cohesion in text and tutorial dialogue

Abstract: Discourse cohesion is presumably an important facilitator of comprehension when individuals read texts and holdconversations. This study investigated components of cohesion and language in different types of discourse about Newtonian physics: A textbook, textoids written by experimental psychologists, naturalistic tutorial dialogue between expert human tutors and college students, and AutoTutor tutorial dialogue between a computer tutor and students (AutoTutor is an animated pedagogical agent that helps studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 20 publications
1
14
0
1
Order By: Relevance
“…This traditional granularity uses the individual as the unit of analysis both to understand behavioural characteristics of individuals working within groups and to measure performance or knowledge-building outcomes of the individuals' in-group contexts. However, the present findings support the claims of many in the computer supported collaborative learning (CSCL) community to also consider group levels of granularity in discourse tracking (Graesser, Jeon, Yan, & Cai, 2007).…”
Section: Prediction and Detectionsupporting
confidence: 79%
“…This traditional granularity uses the individual as the unit of analysis both to understand behavioural characteristics of individuals working within groups and to measure performance or knowledge-building outcomes of the individuals' in-group contexts. However, the present findings support the claims of many in the computer supported collaborative learning (CSCL) community to also consider group levels of granularity in discourse tracking (Graesser, Jeon, Yan, & Cai, 2007).…”
Section: Prediction and Detectionsupporting
confidence: 79%
“…Voyant was used to analyse the text using the following statistics: frequency, Z score and normalized use per 10,000 words. These statistics were used to enable comparison across hubs which may have different volumes of discussion (Graesser, Jeon, Yan, & Cai, 2007). The highest ranked 100 words by raw and normalized frequency were identified in each hub and reviewed to determine terms that relate to specific Bournemouth destination elements.…”
Section: Stage 3: Content Analysis In the Community Of Interestmentioning
confidence: 99%
“…This form of (deictic) cross-referencing can be understood as a way to establish coherence, through the use of cohesive links (Halliday & Hasan, 1976). Extensive research in the Hallidayan tradition has shown that cohesive links in the text contribute to the perceived coherence of a document.…”
Section: Introductionmentioning
confidence: 98%
“…In order to quantify the effect of reference between text and depictive material, we first classified different types of reference, following work on cohesion by Halliday & Hasan (1976). We present a summary of cohesion in text, and our classification of reference types, in Section 3.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation